Scalable preparation of functionalized graphite nanoplatelets via magnetic grinding as lubricity-enhanced additive - Ji, Hai-bin; He, Zhi-wei; Song, Sha-sha; Zhao, Zeng-dian (Journal of Central South University, 2016)
Graphite nanoplatelets were prepared by a novel magnetic-grinding method using self-made equipments. Under a variant magnetic field, magnetic needles collided at a high rotating speed and exfoliated pristine graphite into graphite nanoplatelets with high efficiency. The obtained graphite nanoplatelets are highly crystalline, and the thickness is less than 10 nm. Moreover, the surface area could reached 738.1 m 2 /g with a grinding time of 4 h. Silanized graphite nanoplatelets can disperse well in SG 15W-40 engine oil and serve as lubricant additive. Tribological results indicate that the friction coefficient and wear-scar of the friction pairs are lower than 76% and 41%, respectively, by adding 1.5‰ (mass fraction) of silanized graphite nanoplatelets. Notably, the functionalized graphite nanoplatelets can realize large-scale production and commercial application.